Computer simulation and dynamic modeling of a quadrupedal pronking gait robot with SLIP model - Soyguder, Servet; Alli, Hasan (Pergamon-Elsevier Science Ltd, 2012)
In this study, a quadrupedal pronking gait robot modeling was carried out with Spring Loaded Inverted Pendulum model in stance phase. This is achieved by solving a natural problem in which the main goal is to enable the robot to walk and run in a stable condition regardless of the environmental conditions. In order to solve this problem, dynamic model and control of a quadrupedal robot were realized for a pronking gait. The stance and flight phase dynamic structures were solved in a sequential closed loop to obtain the equation of motion for pronking gait. Spring Loaded Inverted Pendulum model was used as a dynamic model to simplify the simulation, dynamic locomotion and experimental works of the system, and also to simplify the pronking gait concept. The quadrupedal robot with pronking gait was controlled by proportional-derivative control algorithm. As a result, all computer simulations have shown that the proposed control actions and methods are more effective and make the system control quite easy and successful. Crown Copyright (C) 2011 Published by Elsevier Ltd. All rights reserved.
Keywords: Walking Machines